Oral Administration of Semicarbazide Limits Weight Gain together with Inhibition of Fat Deposition and of Primary Amine Oxidase Activity in Adipose Tissue - Josep Mercader; Zsuzsa Iffiú-Soltész; Sandy Bour; Christian Carpéné (Journal of Obesity)
An enzyme hitherto named semicarbazide-sensitive amine oxidase (SSAO), involved in the oxidation of primary amines, is abundantly expressed in adipocytes. Although SSAO physiological functions remain unclear, several molecules inhibiting its activity have been described to limit fat accumulation in preadipocyte cultures or to reduce body weight gain in obese rodents. Here, we studied whether oral administration of semicarbazide, a prototypical SSAO inhibitor, limits fat deposition in mice. Prolonged treatment with semicarbazide at 0.125% in drinking water limited food and water consumption, hampered weight gain, and deeply impaired fat deposition. The adiposomatic index was reduced by 31%, while body mass was reduced by 15%. Such treatment completely inhibited SSAO, but did not alter MAO activity in white adipose tissue. Consequently, the insulin-like action of the SSAO substrate benzylamine on glucose transport was abolished in adipocytes from semicarbazide-drinking mice, while their insulin sensitivity was not altered. Although semicarbazide is currently considered as a food contaminant with deleterious effects, the SSAO inhibition it induces appears as a novel concept to modulate adipose tissue development, which is promising for antiobesity drug discovery.